THE EFFECTIVENESS OF CONTEXTUAL INQUIRY METHOD AND INDEPENDENT CURRICULUM LEARNING MEDIA IN LEARNING ISLAMIC RELIGIOUS EDUCATION AND ETHICS CLASS VII IN PUBLIC JUNIOR HIGH SCHOOL 4 KENDARI - Maulidiah, Dwi; Sumiati, Sumiati; Palangkey, Rahmi Dewanti (JICSA : Journal of Islamic Civilization in Southeast Asian, 2024)
The purpose of this study discuss the Effectiveness of the Contextual Inquiry Method and Independent Curriculum Learning Media in Learning Islamic Religious Education and Ethics Class VII at SMP Negeri 4 Kendari to analyze several things, namely: The application of the Independent Curriculum Learning Media, Effectiveness of the Contextual Inquiry Method in Learning Islamic Religious Education and Budi Pekerti, Finding what factors are an obstacle to the use of the Contextual Inquiry Method and the Independent Curriculum Learning Media in Learning Islamic Religious Education and Budi Pekerti Class VII at SMP Negeri 4 Kendari. This research is a qualitative descriptive research. The researcher used three data collection methods: interview, observation, and documentation. While analyzing the data, the researcher uses a method that includes three steps: data reduction, data presentation, and data verification.